Securing health for all : dimensions and challenges / edited by Sujata Prasad, C. Sathyamala. - Prasad, Sujata.; Sathyamala, C. (Institute for Human Development, 2006)
Contributed articles with reference to India; consultation sponsored by the Human Development Resource Centre of UNDP.